Parallel Discrete Fourier Transform Algorithm Analysis - Kazlauskas, K. (Elektronika ir Elektrotechnika, 2005)
Discrete Fourier transform is widely used for digital signal processing. In the paper, a parallel discrete Fourier transform algorithm is analysed. The algorithm, as compared with the direct discrete Fourier transform algorithm, has a considerably smaller number of operations and increased processing speed. The parallel algorithm can be realised in a parallel manner using fast Fourier transform processors. The complexity of the parallel discrete Fourier transform algorithm is discussed. The optimal number of the fast Fourier transform processors is found. It is shown that the hardware realization of the parallel discrete Fourier transform algorithm is more complicated, because it uses more than one processor, but considerably faster as compared with nonparallel hardware realization of the fast Fourier transform algorithm. Bibl. 5 (in Lithuanian; summaries in Lithuanian, English, Russian).